Nuts and Bolts of a POCUN Program - Noelle M. Northcutt; Nathaniel Reisinger (CINQUILL Medical Publishers Inc., 2022)
For those that have experienced how much point of care ultrasound can positively impact patient care, the potential of an organized point of care ultrasound program is moderated by the reality of building such a program from scratch. We have watched novice and intermediate users ride the roller coaster of ambition and reality checks at each of the hands-on skills sessions across the nation. The first climb occurs on the morning of Day 1. Anticipation grows over how hard it might be to learn this skill, then peaks and dips into the exhilaration of seeing success with what feels like minimal guidance. A comprehension of attainability takes over, and after each hands-on session, confidence climbs fast. Day 2 begins with the courage of some experience, and the anticipation of more success.